Child with post COVID MISC presenting with atypical Kawasaki like features in a rural medical college - Ravivarma, Poovendhan; Vijayakumar, Vimalraj; Ramanathan, . (International Journal of Contemporary Pediatrics, 2021)
COVID-19 in pediatric population is often milder but a segment of cases tend to worsen out and present with pediatric multi system inflammatory syndrome. Here we present a 3 year-old female child presenting with acute febrile illness, generalized rashes with loose stools. On examination child was in fluid refractory shock requiring vasoactives, oxygen by non-rebreather mask, antibiotics and other supportive. Investigations revealed neutrophilic leukocytosis, with normal absolute lymphocyte count, thrombocytopenia and elevated inflammatory markers with negative COVID real time-polymerase chain reaction (RT PCR) and positive COVID immunoglobulin G (IgG) antibody, suggesting a post COVID-19 sequelae. Children presenting with multisystem inflammatory syndrome in children (MIS-C) most often have a silent course of acute COVID infection. Lymphopenia and thrombocytosis are not always associated with MIS-C. COVID antibody with inflammatory markers like C-reactive protein (CRP), D-dimer plays an important role in the management and during follow up. More pediatric studies are needed regarding the role of aspirin in MIS-C with Kawasaki disease overlap, choice of anticoagulant in a thrombocytopenic child and any markers which could predict the development of MIS-C during acute COVID infection.